Hamlet and Emotions
XXV, 347 p. 4 illus.
Keywords: This volume bears potent testimony, not only to the dense complexity of Hamlet’s emotional dynamics, but also to the enduring fascination that audiences, adaptors, and academics have with what may well be Shakespeare’s moodiest play. Its chapters explore emotion in Hamlet, as well as the myriad emotions surrounding Hamlet’s debts to the medieval past, its relationship to the cultural milieu in which it was produced, its celebrated performance history, and its profound impact beyond the early modern era. Its component chapters are not unified by a single methodological approach. Some deal with a single emotion in Hamlet, while others analyse the emotional trajectory of a single character, and still others focus on a given emotional expression (e.g., sighing or crying). Some bring modern methodologies for studying emotion to bear on Hamlet, others explore how Hamlet anticipates modern discourses on emotion, and still others ask how Hamlet itself can complicate and contribute to our current understanding of emotion.